2012
DOI: 10.1371/journal.pone.0043460
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton Multispectral Fluorescence Lifetime Tomography for the Evaluation of Basal Cell Carcinomas

Abstract: We present the first detailed study using multispectral multiphoton fluorescence lifetime imaging to differentiate basal cell carcinoma cells (BCCs) from normal keratinocytes. Images were acquired from 19 freshly excised BCCs and 27 samples of normal skin (in & ex vivo). Features from fluorescence lifetime images were used to discriminate BCCs with a sensitivity/specificity of 79%/93% respectively. A mosaic of BCC fluorescence lifetime images covering >1 mm2 is also presented, demonstrating the potential for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 27 publications
2
33
0
1
Order By: Relevance
“…[12], and in humans, e.g. [13] where studies of skin autofluorescence parameters including lifetime have been correlated with cancer [14,15]. We are interested to apply FLIM to detect and monitor disease in internal organs such as the colon, for which flexible endoscope-based-instrumentation is required and where we believe that FLIM could complement current techniques such as white light endoscopy.…”
Section: Biophotonicsmentioning
confidence: 99%
“…[12], and in humans, e.g. [13] where studies of skin autofluorescence parameters including lifetime have been correlated with cancer [14,15]. We are interested to apply FLIM to detect and monitor disease in internal organs such as the colon, for which flexible endoscope-based-instrumentation is required and where we believe that FLIM could complement current techniques such as white light endoscopy.…”
Section: Biophotonicsmentioning
confidence: 99%
“…FLIM of autofluorescence has potential as a label-free clinical diagnostic tool for in vivo optical biopsies, in particular for skin (Dancik et al, 2013;Galletly et al, 2008;Patalay et al, 2012;Sanchez et al, 2010Sanchez et al, , 2012Seidenari et al, 2012). These 3-dimensional optical biopsies do not require any removal of tissue samples, or any other mechanical or chemical treatment.…”
Section: Flim Of Autofluorescence Of Tissue Eyes and Teethmentioning
confidence: 99%
“…Fluorescence intensity and FLIM images were collected from 27 normal skin samples and 19 excised BCCs, using four emission spectral channels: blue, green, yellow and red. They reported that with this technique, detecting BCCs was accomplished with a sensitivity and specificity of 79 and 93%, respectively [19].…”
Section: • Multispectral Fluorescence Lifetime Tomographymentioning
confidence: 99%